2016
DOI: 10.1352/1944-7558-121.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking Abilities in Adolescents With 22q11.2 Deletion Syndrome: Results From an Experimental Ecological Paradigm

Abstract: The 22q11.2 deletion syndrome (22q11.2DS) is associated with cognitive and functional impairments and increased risk for schizophrenia. We characterized multitasking abilities of adolescents with 22q11.2DS using an experimental naturalistic setting and examined whether multitasking impairments were associated with real-world functioning and negative symptoms. Thirty-nine adolescents (19 with 22q11.2DS and 20 controls) underwent the Multitasking Evaluation for Adolescents. Real-world functioning and clinical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Second, participants with 22q11.2DS were found to check the fuel gauge significantly less often than the controls. This deficient checking behaviour is in agreement with what Schneider et al (2016) observed in a study on multitasking in which adolescents with 22q11.2DS were found to check the time less often (note, however, that PM needs to be Prospective memory in 22q11.2 DS 15 differentiated from multitasking, see McDaniel & Einstein, 2007, for more details).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, participants with 22q11.2DS were found to check the fuel gauge significantly less often than the controls. This deficient checking behaviour is in agreement with what Schneider et al (2016) observed in a study on multitasking in which adolescents with 22q11.2DS were found to check the time less often (note, however, that PM needs to be Prospective memory in 22q11.2 DS 15 differentiated from multitasking, see McDaniel & Einstein, 2007, for more details).…”
Section: Discussionsupporting
confidence: 89%
“…Rather we suggest that people with 22q11.2DS might show PM deficits due to difficulties managing the prospective component of the task, which requires time managing or time monitoring. In a paper on multitasking, Schneider et al (2016) found that people with 22q11.2DS checked the time less frequently than controls during the tasks. For this reason, time-based PM might be more sensitive than event-based PM to detect PM impairments in 22q11.2DS as it requires controlled checking behaviours.…”
Section: Prospective Memory In 22q112 Dsmentioning
confidence: 98%
“…Diminished attention was observed to be proportional to deficits in overall intellectual function. Schneider et al [33] identified impaired multitasking abilities that were attributable to a combination of deficits in working memory and difficulties maintaining concentration on task execution rather than overall intellectual functioning. This additional layer of difficulty in higherorder executive functions suggests a more complex cognitive deficit in 22q11.2DS, impacting not just isolated cognitive processes but also the integration and pragmatic application of these processes in daily life.…”
Section: Executive Functioning and Attentional Processesmentioning
confidence: 99%
“…Indeed, social interactions are complex phenomena that require immediate adaptation to others and an ability to maintain focus on the current conversation while inhibiting irrelevant information [10]. EF deficits may thus contribute substantially to social impairments in general, and in 22q11.2DS patients in particular [8] [11].…”
Section: Social Impairment In 22q112dsmentioning
confidence: 99%